The Voltammetry and Electroanalysis of Some Estrogenic Compounds at Modified Diamond Electrodes - Gan, P; Compton, R; Foord, J (2013)
The voltammetry of some estrogenic compounds (estradiol, nonylphenol, bisphenol A, ethynylestradiol, estrone, estriol) in aqueous solution at boron doped diamond electrodes is reported. For oxidised (hydrophilic) electrodes electrochemically irreversible kinetics were observed for the diffusing molecules allowing the inference of diffusion coefficients and transfer coefficients. In contrast for hydrogen terminated (hydrophobic) surfaces significant adsorption was observed. A limit of detection of 1-100μM for the estrogenic compounds was found using the oxidised diamond electrode. Surface modification of the oxidised diamond with nano-Carbon (so-called Carbon Black) allowed preconcentration of the target by adsorption onto the Carbon Black prior to analysis and a corresponding reduction of the limit of detection by ca three orders of magnitude to 5-100nM. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.